An Experimental Study of High-Pressure Microscopy and Enhanced Oil Recovery with Nanoparticle-Stabilised Foams in Carbonate Oil Reservoir - Ayomikun Bello; Anastasia Ivanova; Alexander Rodionov; Timur Aminev; Alexander Mishin; Denis Bakulin; Pavel Grishin; Pavel Belovus; Artem Penigin; Konstantin Kyzyma; Alexey Cheremisin (Energies, 2023)
Foams have been successfully implemented to overcome the challenges associated with gas-enhanced oil recovery (EOR) over time. Generally, the foam helps to increase the viscosity of the injected gas, which in turn improves the effectiveness of EOR. However, this technology has rarely been applied in the oilfield due to technological and economical limitations. It is widely considered that nanoparticles may be added to foam to enhance its performance in harsh reservoir conditions to overcome some of these limitations. In this study, we employed high-pressure microscopy (HPM) as an advanced technique to examine the stability of <semantics>N2</semantics> and <semantics>CO2</semantics> foams at reservoir conditions, both with and without nanoparticles. The experiments were conducted under vapour and supercritical conditions. Our results indicated that foams produced at 80% quality were more stable than foams produced at 50% quality because the bubble size was significantly smaller and the bubble count was higher. Additionally, foams under supercritical conditions (sc) exhibited greater stability than foams under vapour conditions. This is because at supercritical conditions, the high density of gases helps to strengthen the foam lamella by enhancing the intermolecular contacts between the gas and the hydrophobic part of the liquid phase. Furthermore, core flooding studies were performed to investigate their effect on oil displacement and mobility control in both real and artificial core samples. Rather than focusing on precise quantitative results, our objective was to assess the effect of foams on oil recovery qualitatively. The results indicated that foam injection could significantly increase displacement efficiency, as foam injection raised total displacement efficiency from an initial 48.9% to 89.7% in the artificial core sample. Similarly, in the real core model, <semantics>CO2</semantics> foam injection was implemented as a tertiary recovery method, and a recovery factor of 28.91% was obtained. These findings highlight the potential benefits of foams for EOR purposes and their ability to mitigate early gas breakthrough, which was observed after injecting approximately 0.14 PV during <semantics>scCO2</semantics> injection.